Comparison Of The Effectiveness Of Crystalloid And Colloid Infusion Fluids In Patients With Hypovolemic Shock - Angriawan Angriawan; Reghula Maryeti Sandra; Yudi Muammar (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Hypovolemic shock is an emergency condition resulting from significant fluid volume loss, resulting in decreased tissue perfusion . The primary treatment is fluid resuscitation using crystalloid or colloid fluids. This study aims to compare the effectiveness of crystalloid and colloid infusion fluids in patients with hypovolemic shock . The research method used a quantitative approach with a quasi-experimental design . A sample of 80 patients was divided into two groups (crystalloid and colloid). Parameters measured included blood pressure, pulse rate, and cardiac output. urine . The results showed that both fluids were effective in improving hemodynamic conditions , but colloid fluids showed a faster increase in blood pressure (p<0.05). It was concluded that colloid fluids were more effective in initial stabilization, but crystalloids remained the primary choice due to safety and cost factors. Keywords: Hypovolemic Shock , Crystalloids, Colloids, Fluid Resuscitation